Anna Pacześniak, Bartosz Rydliński (red.), Europejskie partie polityczne. Dyskurs programowy w Unii Europejskiej, Warszawa 2021, Wydawnictwo Sejmowe, ss. 302. - Kruk, Aleksandra (Rocznik Integracji Europejskiej, 2021)
Recenzja